Agarose, Alginate and Chitosan Nanostructured Aerogels for Pharmaceutical Applications: A Short Review - Guastaferro, Mariangela; Reverchon, Ernesto; Baldino, Lucia (Frontiers in Bioengineering and Biotechnology, 2021)
In this short review, drug delivery systems, formed by polysaccharide-based (i.e., agarose, alginate, and chitosan) aerogels, are analyzed. In particular, the main papers, published in the period 2011–2020 in this research field, have been investigated and critically discussed, in order to highlight strengths and weaknesses of the traditional production techniques (e.g., freeze-drying and air evaporation) of bio-aerogels with respect to supercritical CO2 assisted drying. Supercritical CO2 assisted drying demonstrated to be a promising technique to produce nanostructured bio-aerogels that maintain the starting gel volume and shape, when the solvent removal occurs at negligible surface tension. This characteristic, coupled with the possibility of removing also cross-linking agent residues from the aerogels, makes these advanced devices safe and suitable as carriers for controlled drug delivery applications.